Soft system methodology approach: Tourism conceptual model as the identity of Bandung, Indonesia - Leo Aldianto; Santi Novani; Grisna Anggadwita; Adi Asmariadi Budi; Christina Wirawan (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The Indonesian tourism sector has become one of government's focus points because of its significant contribution to economic development on all levels, district/city, province, or national. As an Indonesian city, Bandung has a lot of tourism potential with its local cultural diversity. The purpose of this research is to develop a conceptual model design of tourism, especially in Bandung city as one of the cultural identity cities in West Java. A system thinking approach with qualitative analysis, known as the Soft System Methodology (SSM), is used in this research. Qualitative data collection techniques were carried out by a purposive sampling technique which was obtained from the results of in-depth interviews with stakeholders that included academics, representatives of the government, communities, and businesspeople in the tourism sector. The result of this research is a conceptual model design for Bandung city tourism as the identity of a cultural city, called as Sunda Culture Center (Sunda Centrum).
Keywords: 650; conceptual model; local culture; soft system methodology; stakeholders; Sunda centrum; tourism